Phase-field study of size-dependent morphology of austenite–twinned martensite interface in CuAlNi. (15th October 2016) - Tůma, K.; Stupkiewicz, S.
Highlights: Phase-field model of martensitic transformation at finite strain. Detailed study of austenite-twinned martensite interface in CuAlNi shape memory alloy. Effect of twin spacing on the morphology and energy of the transition layer. Competition between the interfacial energy and the energy of elastic micro-strains. Two mechanisms are revealed: formation of zigzag-shaped interface and twin branching. Graphical abstract: Abstract: Size-dependent microstructure of the interface layer between austenite and twinned martensite is studied using a recently developed finite-strain phase-field model. The microstructure is assumed periodic and two-dimensional, however, non-zero out-of-plane displacements are allowed so that the basic microstructural features, specifically the nominal orientation of the twinning and habit planes and the twin fraction, are consistent with the crystallographic theory of martensite. The phase-field computations are carried out for the CuAlNi shape memory alloy undergoing the cubic-to-orthorhombic transformation, and the corresponding four crystallographically distinct microstructures of the austenite–twinned martensite interface are studied in detail. The focus is on size-dependent morphology of the interface layer and on size-dependent interfacial and elastic micro-strain energy contributions. Two mechanisms of reducing the elastic micro-strain energy are revealed: formation of a non-planar zigzag-like interface and twin branching.